Spectrofluorimetry in organized media coupled to second-order multivariate calibration for the determination of galantamine in the presence of uncalibrated interferences - Culzoni, Maria Julia (2010)
The present article describes the spectrofluorimetric determination of galantamine, a widely used acetylcholinesterase inhibitor, through excitation–emission fluorescence matrices and second-order calibration. With the purpose of enhancing the fluorescence intensity of this substance, the effect of different organized assemblies was evaluated. Although the interaction of galantamine with different cyclodextrins is weak, it was corroborated that the fluorescence intensity of this pharmaceutical in the presence of -cyclodextrin is increased by a twofold factor. Among the studied micellar media, the anionic surfactant sodium dodecyl sulfate produced the largest signals for the compound of interest (sixfold enhancement), and was selected as auxiliary reagent for the subsequent determinations. The developed approach enabled the determination of galantamine at the ngmL−1 level without the necessity of applying separation steps, and in the presence of uncalibrated interferences. The applied second-order chemometric tools were parallel factor analysis (PARAFAC), unfolded partial least-squares coupled to residual bilinearization (U-PLS/RBL), and multidimensional partial least-squares coupled to residual bilinearization (N-PLS/RBL). The ability of U-PLS/RBL to successfully overcome spectral interference problems is demonstrated. The quality of the proposed method was established with the determination of galantamine in both artificial and natural water samples.